Vermicompost+inorganic fertilizers promote yield and nutrient uptake of amaranth (Amaranthus tricolor L.) - Preetha, D.; Sushama, P.K.; Marykutty, K.C. (Journal of Tropical Agriculture, 2006)
A field trial on amaranth (Amaranthus tricolor L.) with different levels of vermicompost prepared using ayurvedic pharmaceutical wastes (from Oushadhi Pharmaceuticals, Thrissur), farm yard manure (FYM) and inorganic fertilizers was conducted. Five tonnes of vermicompost together with 50:50:50 N, P2O5, K2O kg ha-1 gave the highest vegetative yield as well as nutrient uptake, followed by 2.5 t ha-1 of vermicompost+NPK, implying the synergistic effects of combined application of vermicompost and chemical fertilizers in amaranth production.